2017
DOI: 10.1002/lary.26745
|View full text |Cite
|
Sign up to set email alerts
|

A population‐based analysis of verrucous carcinoma of the oral cavity

Abstract: 4. Laryngoscope, 128:393-397, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 25 publications
2
36
0
Order By: Relevance
“…The average age at diagnosis was 52.3 years in our cohort, similar to that reported in previous articles 11,12 . Advanced age has long been recognized as a poor prognostic factor for most known malignancies, possibly because of a higher prevalence of concomitant medical comorbidities 16–18 . In our study, age >65 was also identified as an independent prognostic factor associated with worse OS and DSS.…”
Section: Discussionsupporting
confidence: 88%
“…The average age at diagnosis was 52.3 years in our cohort, similar to that reported in previous articles 11,12 . Advanced age has long been recognized as a poor prognostic factor for most known malignancies, possibly because of a higher prevalence of concomitant medical comorbidities 16–18 . In our study, age >65 was also identified as an independent prognostic factor associated with worse OS and DSS.…”
Section: Discussionsupporting
confidence: 88%
“…[4][5][6][7][8] Surgical resection remains the primary treatment modality for oral cavity VC, and rates of PORT range from 10% to 18%. 9,10 However, the benefit of PORT is unclear, and may actually reduce survival. In a recent cross-sectional population analysis of the Surveillance, Epidemiology, and End Results (SEER) database, Mohan et al reported that patients treated with PORT trended toward worse overall survival (OS) compared to those treated with surgery alone (71.4 and 117 months, respectively; P = .12).…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] The radiosensitivity of VC is also controversial as adjuvant RT may not be as effective for these indolent tumors compared to conventional SCC. 5,9,17 Given the need for additional data regarding the use of adjuvant RT in the management of oral cavity VC, we present the current utilization of PORT and variables associated with its delivery in the United States. Secondarily, we report survival outcomes in this patient population, including the impact of PORT on OS, which supplements prior database studies.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the pathological differentiation of oral cancer, the verrucous carcinoma, originally described as a variant of SCC, should be considered as a distinct entity, associated with a generally favorable prognosis. The referred neoplasia is more prevalent in the tongue, followed by the alveolar ridge and buccal mucosa …”
Section: Introductionmentioning
confidence: 99%
“…The referred neoplasia is more prevalent in the tongue, followed by the alveolar ridge and buccal mucosa. 12 There are no nationwide data regarding incidence, morbidity, and mortality of tongue cancer in Brazil. To fill the gap, the purpose of the current research was to clarify the scientific community about the trends of tongue cancer epidemiology in the country.…”
Section: Introductionmentioning
confidence: 99%